Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Get quick and reliable answers to your questions from a dedicated community of professionals on our platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Alright! Let's go through the problem step-by-step to find the point [tex]\( P(x, y) \)[/tex] such that the distances from [tex]\( P \)[/tex] to [tex]\( A \)[/tex] and [tex]\( B \)[/tex] are equal, and [tex]\( P \)[/tex] lies on the given line [tex]\( 10x - 12y - 15 = 0 \)[/tex].
Given points:
- [tex]\( A = (4, 3) \)[/tex]
- [tex]\( B = (-1, -3) \)[/tex]
- The equation of the line: [tex]\( 10x - 12y - 15 = 0 \)[/tex]
We are asked to find point [tex]\( P(x, y) \)[/tex] such that:
1. [tex]\( PA = PB \)[/tex]
2. Point [tex]\( P \)[/tex] satisfies the line equation [tex]\( 10x - 12y - 15 = 0 \)[/tex]
### Step 1: Establish the distance equality
Firstly, we'll use the distance formula to express [tex]\( PA \)[/tex] and [tex]\( PB \)[/tex]:
[tex]\[ PA = \sqrt{(x - 4)^2 + (y - 3)^2} \][/tex]
[tex]\[ PB = \sqrt{(x + 1)^2 + (y + 3)^2} \][/tex]
### Step 2: Equate the distances
Given [tex]\( PA = PB \)[/tex], we can set up the following equation:
[tex]\[ \sqrt{(x - 4)^2 + (y - 3)^2} = \sqrt{(x + 1)^2 + (y + 3)^2} \][/tex]
Square both sides to eliminate the square roots:
[tex]\[ (x - 4)^2 + (y - 3)^2 = (x + 1)^2 + (y + 3)^2 \][/tex]
### Step 3: Expand both sides
Expand the expressions:
[tex]\[ (x^2 - 8x + 16) + (y^2 - 6y + 9) = (x^2 + 2x + 1) + (y^2 + 6y + 9) \][/tex]
Simplify by combining like terms:
[tex]\[ x^2 - 8x + 16 + y^2 - 6y + 9 = x^2 + 2x + 1 + y^2 + 6y + 9 \][/tex]
Remove [tex]\( x^2 \)[/tex] and [tex]\( y^2 \)[/tex] from both sides, since they are equal:
[tex]\[ -8x + 16 - 6y + 9 = 2x + 1 + 6y + 9 \][/tex]
Combine all constant terms:
[tex]\[ -8x - 6y + 25 = 2x + 6y + 10 \][/tex]
Combine like terms involving [tex]\( x \)[/tex] and [tex]\( y \)[/tex]:
[tex]\[ -8x - 2x - 6y - 6y = 10 - 25 \][/tex]
Simplify further:
[tex]\[ -10x - 12y = -15 \][/tex]
Which simplifies to:
[tex]\[ 10x + 12y = 15 \][/tex]
### Step 4: Incorporate the given line equation
Given point [tex]\( P \)[/tex] lies on the line [tex]\( 10x - 12y - 15 = 0 \)[/tex], this is already our second equation.
Thus, the solution for [tex]\( P \)[/tex] should satisfy:
1. [tex]\( 10x + 12y = 15 \)[/tex]
2. [tex]\( 10x - 12y - 15 = 0 \)[/tex]
### Step 5: Solve the system of equations
Add the two equations:
[tex]\[ (10x + 12y) + (10x - 12y) = 15 + 15 \][/tex]
[tex]\[ 20x = 30 \][/tex]
[tex]\[ x = \frac{30}{20} = \frac{3}{2} \][/tex]
Substitute [tex]\( x = \frac{3}{2} \)[/tex] back into the line equation [tex]\( 10x - 12y - 15 = 0 \)[/tex]:
[tex]\[ 10 \left(\frac{3}{2}\right) - 12y - 15 = 0 \][/tex]
[tex]\[ 15 - 12y - 15 = 0 \][/tex]
Solve for [tex]\( y \)[/tex]:
[tex]\[ -12y = 0 \][/tex]
[tex]\[ y = 0 \][/tex]
Therefore, the point [tex]\( P \)[/tex] is:
[tex]\[ \left( \frac{3}{2}, 0 \right) \][/tex]
Given points:
- [tex]\( A = (4, 3) \)[/tex]
- [tex]\( B = (-1, -3) \)[/tex]
- The equation of the line: [tex]\( 10x - 12y - 15 = 0 \)[/tex]
We are asked to find point [tex]\( P(x, y) \)[/tex] such that:
1. [tex]\( PA = PB \)[/tex]
2. Point [tex]\( P \)[/tex] satisfies the line equation [tex]\( 10x - 12y - 15 = 0 \)[/tex]
### Step 1: Establish the distance equality
Firstly, we'll use the distance formula to express [tex]\( PA \)[/tex] and [tex]\( PB \)[/tex]:
[tex]\[ PA = \sqrt{(x - 4)^2 + (y - 3)^2} \][/tex]
[tex]\[ PB = \sqrt{(x + 1)^2 + (y + 3)^2} \][/tex]
### Step 2: Equate the distances
Given [tex]\( PA = PB \)[/tex], we can set up the following equation:
[tex]\[ \sqrt{(x - 4)^2 + (y - 3)^2} = \sqrt{(x + 1)^2 + (y + 3)^2} \][/tex]
Square both sides to eliminate the square roots:
[tex]\[ (x - 4)^2 + (y - 3)^2 = (x + 1)^2 + (y + 3)^2 \][/tex]
### Step 3: Expand both sides
Expand the expressions:
[tex]\[ (x^2 - 8x + 16) + (y^2 - 6y + 9) = (x^2 + 2x + 1) + (y^2 + 6y + 9) \][/tex]
Simplify by combining like terms:
[tex]\[ x^2 - 8x + 16 + y^2 - 6y + 9 = x^2 + 2x + 1 + y^2 + 6y + 9 \][/tex]
Remove [tex]\( x^2 \)[/tex] and [tex]\( y^2 \)[/tex] from both sides, since they are equal:
[tex]\[ -8x + 16 - 6y + 9 = 2x + 1 + 6y + 9 \][/tex]
Combine all constant terms:
[tex]\[ -8x - 6y + 25 = 2x + 6y + 10 \][/tex]
Combine like terms involving [tex]\( x \)[/tex] and [tex]\( y \)[/tex]:
[tex]\[ -8x - 2x - 6y - 6y = 10 - 25 \][/tex]
Simplify further:
[tex]\[ -10x - 12y = -15 \][/tex]
Which simplifies to:
[tex]\[ 10x + 12y = 15 \][/tex]
### Step 4: Incorporate the given line equation
Given point [tex]\( P \)[/tex] lies on the line [tex]\( 10x - 12y - 15 = 0 \)[/tex], this is already our second equation.
Thus, the solution for [tex]\( P \)[/tex] should satisfy:
1. [tex]\( 10x + 12y = 15 \)[/tex]
2. [tex]\( 10x - 12y - 15 = 0 \)[/tex]
### Step 5: Solve the system of equations
Add the two equations:
[tex]\[ (10x + 12y) + (10x - 12y) = 15 + 15 \][/tex]
[tex]\[ 20x = 30 \][/tex]
[tex]\[ x = \frac{30}{20} = \frac{3}{2} \][/tex]
Substitute [tex]\( x = \frac{3}{2} \)[/tex] back into the line equation [tex]\( 10x - 12y - 15 = 0 \)[/tex]:
[tex]\[ 10 \left(\frac{3}{2}\right) - 12y - 15 = 0 \][/tex]
[tex]\[ 15 - 12y - 15 = 0 \][/tex]
Solve for [tex]\( y \)[/tex]:
[tex]\[ -12y = 0 \][/tex]
[tex]\[ y = 0 \][/tex]
Therefore, the point [tex]\( P \)[/tex] is:
[tex]\[ \left( \frac{3}{2}, 0 \right) \][/tex]
We appreciate your time. Please come back anytime for the latest information and answers to your questions. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.